Conflict experiences and household expectations on recovery: Survey evidence from northern Uganda - Carlos Bozzoli; Tilman Brück; Tony Muhumuza (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We analyse the role of mass violent conflict in influencing individual expectations. We hypothesise that individuals are likely to report negative expectations if they were exposed to conflict events in the past. We combine individual and household level data from the Northern Uganda Livelihood Survey of 2007 with a disaggregated conflict exposure index based on the Armed Conflict Locations Events Data (ACLED). We run logistic regression models to study the strength of the association between conflict and expectations. Results indicate that conflict intensity is correlated with a decrease in the probability of expecting economic recovery. The effect of conflict on general welfare however is less robust.
Keywords: D84; H56; O10; 330; Conflict; Expectations; War; Welfare; Politischer Konflikt; Erwartungstheorie; Konjunktur; Schätzung; Uganda